RAS-challenge as a first-look test for detection of primary aldosteronism in patients with treatment-resistant hypertension - Christian Beger; Theresa Karg; Jan B. Hinrichs; Bastian Ringe; Hermann Haller; Bernhard C. Meyer; Florian P. Limbourg (Blood Pressure, 2023)
Purpose Primary aldosteronism (PA), characterised by low-renin hypertension, confers a high cardiovascular risk and is the most common cause of secondary hypertension, with an increased prevalence in patients with treatment-resistant hypertension. However, it is estimated that only a small percentage of affected patients are identified in routine clinical practice. Inhibitors of the renin-angiotensin system cause an increase in renin levels in patients with intact aldosterone regulation, and inadequate low renin with concurrent RAS inhibition (RASi) may therefore indicate PA, which could serve as a first look screening test for selection for formal work-up. Methods We analysed patients between 2016–2018 with treatment-resistant hypertension who had inadequate low renin in the presence of RASi (i. e. at risk for PA) and who were offered systematic work-up with adrenal vein sampling (AVS). Results A total of 26 pts were included in the study (age 54.8 ± 11, male 65%). Mean office blood pressure (BP) was 154/95 mmHg on 4.5 antihypertensive drug classes. AVS had a high technical success rate (96%) and demonstrated unilateral disease in the majority of patients (57%), most of which (77%) were undetected by cross-sectional imaging. Conclusion In patients with resistant hypertension, low renin in the presence of RASi is a strong indicator for autonomous aldosterone secretion. It may serve as an on-medication screening test for PA to select for formal PA work up.